Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/w8040120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Non-Stationary Effects of Forests and Developed Land within Watersheds on Biological Indicators of Streams Using Geographically-Weighted Regression

Abstract: This study examined the non-stationary relationship between the ecological condition of streams and the proportions of forest and developed land in watersheds using geographically-weighted regression (GWR). Most previous studies have adopted the ordinary least squares (OLS) method, which assumes stationarity of the relationship between land use and biological indicators. However, these conventional OLS models cannot provide any insight into local variations in the land use effects within watersheds. Here, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
(88 reference statements)
1
18
0
Order By: Relevance
“…At present, most of the studies about the feedback of biomass or the community structure of algae on environmental factors are based on laboratory cultivation, ecological simulation or field sampling [31,32]. However, studies about the impact of land use change-induced water quality disturbances on the biomass and community structures of algae are still not adequate at the regional scale [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most of the studies about the feedback of biomass or the community structure of algae on environmental factors are based on laboratory cultivation, ecological simulation or field sampling [31,32]. However, studies about the impact of land use change-induced water quality disturbances on the biomass and community structures of algae are still not adequate at the regional scale [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…When I is close to −1 or 1, the residuals of the estimated OLS and GWR models are strongly spatially dependent [66], which violates a fundamental assumption of statistical analysis. Lower AICc values indicate a closer approximation of the model to the actual nature of the relationships of dependent variables (i.e., percentage of Japanese red pine trees, elevation, and slope) with a dependent variable (i.e., burn severity) within a grid [37]. ArcMap GIS was used to compute Moran's I-values and visualize the localized variation in the effects of Japanese red pine on burn severity over the study area.…”
Section: Spatial Distribution Of Burn Severity and Percentage Of Japamentioning
confidence: 99%
“…The OLS model (Equation (1)) can be considered a special case of the GWR model (Equation (2)) in which the parameter surface is assumed to be constant over space [36][37][38][50][51][52]. Equation (2) is not a single equation; rather, it comprises an array of equations corresponding to different grid cells.…”
Section: Estimating the Global (Ols) And Local (Gwr) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al [23] examined the non-stationary relationship between the ecological condition of streams and the proportions of forest and developed land in watersheds by using geographically weighted regression (GWR). They found that the GWR model had superior performance compared with the ordinary least squares method model.…”
Section: Contributionsmentioning
confidence: 99%